French and English Phonologies in Contact: The Case of Montreal English - Julie Rouaud (Anglophonia)
More than a third of the whole Anglophone community in Quebec is currently concentrated in Montreal. This rather large linguistic community shows signs of increasing bilingualism due to its contact with the Francophone majority, especially after the 1970s. The contact started as early as the end of the eighteenth century. Therefore, there is reason to wonder about a potential influence of French on varieties of Canadian English that are in contact with French, from a lexical as well as a phonological point of view. The current paper focuses on the hypothesis that the variety of English spoken by the Anglophones in Montreal is more influenced by French than any other varieties of English in Canada. Studying both linguistic communities from a historical perspective sheds light on the current situation of French and English in Montreal. In this study, I rely on a spoken corpus, PAC[Montreal] (Rouaud 2016-2017). PAC[Montreal] follows the PAC Program (Phonologie de l’Anglais Contemporain : usage, variétés, structure) methodology. Spoken data and sociolinguistic metadata gathered from the surveys allow a more accurate description of the linguistic community under scrutiny, while analyzing its phonetico-phonological specificities. Thanks to sociolinguistic information, a classification of the degrees of bilingualism has been created for the fourteen informants in PAC[Montreal]. These degrees are tested in relation to the informants’ performances in their reading and conversational tasks so as to measure the role played by French in Montreal English. Four features that are characteristic of Quebec French are analyzed as markers of francization: assibilation, r-realizations, /y/-realizations and nasal vowels. The analysis of these markers within the three groups tends to confirm that there is a significantly higher rate of francization among bilinguals, suggesting a possible movement towards language mixing for Montreal English. Besides, phonological and acoustic results suggest that interference operates similarly among dominant and balanced bilinguals, questioning the traditional distinction between these two levels of bilingualism.